Agatha Christie no mundo virtual: a recepção de jogos de computador criados a partir de suas obras impressas - Bogusz, Paola Natacha (2011)
The virtual world is in an increasing development and the studies that involve literature and ciberculture appear as something new in an area before marked by the use of printed works. Today it is possible not only to analyse the printed texts but also to associate them to virtual texts and other existing virtual formats. As a consequence, a new way to conceive literature would be by seeing it in a different media, the virtual. Then, this work comes to show that elements present on the printed universe can transit in other media, such as the virtual and still be apreciated and valued, not losing its importance and existence. This research analyses the reception of readers and / or users of four Agatha Christie's books and four computer games which were created based on the books. For that, volunteers answered to a questionaire created with the intention of realizing how the reception process occurs, as well as, to see how the relation between the media works. Translation and adaptation theory was seen with studies from Benjamin (2001), Derrida (2002a & 2002b), Diniz (2003 & 2005) and Amorim (2005). Some elements of multimodality studies theory were researched in works from Lévi (1999), Gee (2007) e Aranha (2008). Iser (1996 & 1999), Compagnon (2001) and Derrida (2002) brought explanations to some repertoire areas.